Pengaruh Kualitas Produk Dan Promosi Terhadap Minat Beli Konsumen - Muhamad Faiz Alawi; H. Ari Arisman; Barin Barlian (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
The purpose of the research and analyze influence Product Quality, Promotion, Consumers Buying Interest in Meubel Zulfami Tasikmalaya City. The method used in this research is method quantitaive descriptive a survey. The research data were obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple regression analysis using SPSS software. The results of this study indicate that the Product Quality, and Promotion simultaneously have a significant effect on Consumers Buying Interest. Product Quality partially significant effect Consumers Buying Interest. promotion has a significant effect on Consumers Buying Interest.